KREATIVITAS GURU DALAM PEMBELAJARAN TEMATIK DI ERA PANDEMI PADA KELAS IV B MI AL-MAARIF 02 SINGOSARI - Siti Ni’matul Umah; Mohammad Afifulloh; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
This thesis discusses the creativity of teachers in thematic learning in the pandemic era in class IV B MI Al-Maarif 02 Singosari. The researchers focused this research on: 1) teacher creativity in managing the classroom during a pandemic. 2) teacher creativity in delivering thematic learning during a pandemic. 3) the teacher's creativity factor in thematic learning during a pandemic. This study used qualitative research methods. the subjects in this study were class IV B teachers, principals, students. data collection using interviews, observation, documentation. The results of this study are the teacher's creative efforts in thematic learning during a pandemic such as managing classes to be conducive and comfortable, delivering learning using various learning methods and media, utilizing technology. as well as factors supporting the creativity of teachers are the facilities and policies provided by the school. while the inhibiting factor is that parents who have limited gadgets must take turns with their children. Keywords: Teacher Creativity, Thematic Learning, Covid-19 Pandemic